“La reticularidad de la información como parte de los contenidos presentados en la plataforma web: caso UNACH, periodo enero-junio 2019”. - Guashpa Sacancela, Silvia Paola (2019)
This research project called “THE RETICULARITY OF INFORMATION AS PART OF THE CONTENTS PRESENTED ON THE WEB PLATFORM: CASE UNACH, PERIOD JANUARY-JUNE 2019”, was carried out in order to know the characteristics of the reticularity and the strategies used to time to distribute the contents on the web platform of the National University of Chimborazo. On the application of the methodology. The scientific, analytical and descriptive methods used; the type of research is documentary-bibliographic and field. On the other hand, the research design is qualitative, so the application of the population and sample was not necessary. Finally, three date collection techniques were used with their respective instruments. Through the application of the macronavigation, micronavigation, and usability matrix, an average score of 4, 3 out of 5 was obtained and in the evaluation matrixes a compliance of 83,2% over 100% was determined with respect to the design and form of the web platform, while in relation to its structure and body, the platform complies with 89,1% over 100%. Additionally, interviews were conducted with three experts from the city, regarding the reticularity of the information. Finally, the importance of the topic “reticularity of information on web platforms” is determined, as this allows the communication of many people and the ability to create network. To reach these conclusions, we start from the concepts of different authors such as: Scolari, Lévy, Mttelart, Salavarría, among others.